The Role of School Guidance and Counselling in Promoting Mental well-being and Critical Thinking among junior Secondary School Students in Anambra State - Chinwe Augustina Enwere (Action Research Journal Indonesia (ARJI), 2026)
Guidance and counselling at school is critical in improving the mental health and critical thinking skills of junior secondary school students. The current research involved a descriptive survey design, which included all of the teachers in the public secondary schools. A sample size of 118 teachers was used. This information was collected using a structured questionnaire administered using the Google Forms platform, and the results were rated in a 4-point Likert scale. The reliability of the instruments was determined by a pilot study, which produced a Cronbach alpha of 0.85. Findings show that guidance and counselling services play a key role in promoting the mental health of students through the emotional support they offer, stress management techniques, and coping. Besides, organised counselling programmes encourage building of critical-thinking capabilities, which help pupils to develop logical thinking, decision-making abilities, and problem-solving skills. This research suggests that more finance should be allocated, more parents should be involved, and policy solutions should be implemented to strengthen school counselling programmes in the State of Anambra.